2010
DOI: 10.1128/mcb.01418-09
|View full text |Cite
|
Sign up to set email alerts
|

The Embryonic Transcription Cofactor LBH Is a Direct Target of the Wnt Signaling Pathway in Epithelial Development and in Aggressive Basal Subtype Breast Cancers

Abstract: Limb-bud and heart (LBH) is a novel key transcriptional regulator of vertebrate development. However, the molecular mechanisms upstream of LBH and its role in adult development are unknown. Here we show that in epithelial development, LBH expression is tightly controlled by Wnt signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
109
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(116 citation statements)
references
References 78 publications
4
109
0
Order By: Relevance
“…We hypothesize that in ER-positive patients with an inactive ER pathway, other pathways such as Wnt or Hedgehog, associated with more aggressive behavior and worse outcome, may actually have been driving tumor growth (1,54,55). This is in agreement with the reported decline in SET index with advancing pathologic cancer stage, despite ER positivity, suggesting decreasing tumor dependency on an active ER pathway (53).…”
Section: Discussionsupporting
confidence: 81%
“…We hypothesize that in ER-positive patients with an inactive ER pathway, other pathways such as Wnt or Hedgehog, associated with more aggressive behavior and worse outcome, may actually have been driving tumor growth (1,54,55). This is in agreement with the reported decline in SET index with advancing pathologic cancer stage, despite ER positivity, suggesting decreasing tumor dependency on an active ER pathway (53).…”
Section: Discussionsupporting
confidence: 81%
“…These findings are highly significant given that in human breast cancer, LBH is aberrantly overexpressed in the most lethal basal tumor subtype (Lamb et al, 2013;Rieger et al, 2010), which is hormone receptor negative and enriched in cancer stem cells (Honeth et al, 2008;Sorlie et al, 2003). Future studies will be necessary to elucidate the precise mechanism by which LBH regulates basal MaSC function and its role in carcinogenesis, as well as to determine its contribution to the stem cell-promoting effects of WNT in normal and neoplastic mammary gland development.…”
Section: Discussionmentioning
confidence: 86%
“…Reduced cell proliferation in TEBs and alveoli of pubertal or pregnant K14-Cre;Lbh loxP/loxP glands, respectively, further suggests that LBH is required for MaSC activation, as these lobular structures are normally enriched in actively proliferating MaSCs (Bai and Rohrschneider, 2010;Williams and Daniel, 1983) and express high levels of LBH Rieger et al, 2010). Although it remains debatable whether unipotent basal and luminal stem cells alone or multi-potent basal MaSCs generate mammary gland epithelium in vivo (van Amerongen et al, 2012;Van Keymeulen et al, 2011;Prater et al, 2014;Rios et al, 2014), in situ stem cell marker analyses (Williams and Daniel, 1983) and in vivo labeling of activated MaSCs using a transgenic SHIP-GFP reporter line (Bai and Rohrschneider, 2010) suggest that activated MaSCs have basal characteristics, including a CD29 lo CD24 + marker profile.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the early stage of vertebrate embryogenesis, LBH regulates the formation of the limbs and heart. Moreover, Rieger et al reported that the WNT signaling pathway can directly target LBH to participate in the occurrence and development of breast cancer [10]. Liu et al showed that nasopharyngeal epithelial cells may initiate malignant transformation due to the Epstein-Barr virus-mediated downregulation of LBH [11].…”
Section: Introductionmentioning
confidence: 99%